Benzo[1, 2-d:4, 5-d′]bisthiazole fluorophores for luminescent solar concentrators: synthesis, optical properties and effect of the polymer matrix on the device performances. (April 2021) - Papucci, Costanza; Dessì, Alessio; Coppola, Carmen; Sinicropi, Adalgisa; Santi, Greta; Di Donato, Mariangela; Taddei, Maria; Foggi, Paolo; Zani, Lorenzo; Reginato, Gianna; Pucci, Andrea; Calamante, Massimo; et al.
Abstract: Three new fluorophores (BBT2-4 ) with a D-A-D structure, characterised by the common benzo[1, 2- d :4, 5- d′ ]bisthiazole (BBT) as acceptor core (A) and different donor groups (D), were designed and synthesised for use in thin-film luminescent solar concentrators (LSC). The optical and spectroscopic properties of the new dyes were analysed both in solution (toluene) and in polymeric films, using static and time-resolved techniques. All the prepared molecules showed intense emissions between 460 and 550 nm with large Stokes shift (>50 nm), moderate-to-good fluorescence quantum yields (Φf ) both in toluene solution (18–73%) and in poly(methyl methacrylate) (PMMA) films (10–52%) and good optical efficiencies (5.8–7.5%) as LSC. Transient absorption spectroscopy (TAS) studies highlighted that higher Φf were related to long excited-state lifetimes and that such properties were critically dependent on the polarity of the surrounding environment. Notably, homogeneous BBT4 dispersions into the less polar poly(benzyl methacrylate) (PBzMA) and poly(cyclohexyl methacrylate) (PCMA) polymeric matrices showed higher Φf (52.6% and 65.6%, respectively) than those gathered from PMMA films. Accordingly, BBT4 /PCMA films revealed significant optical efficiency of 9.0% as LSC, which was comparable to that provided by the state-of-art fluorophore Lumogen Red 305 (10.1%). Graphical abstract: Image 1